A prospective study of breast cancer risk in relatives of BRCA1/BRCA2 mutation carriers - Rowan, Erica; Poll, Aletta; Narod, Steven A (Journal of medical genetics, 2007)
Smith et al reported that 24% of 118 relatives with breast cancer or ovarian cancer cases in 277 families with a BRCA mutation were phenocopies, and they estimated the risk of breast cancer in mutation-negative women to be five times greater than expected. 6 Gronwald et al studied unselected cases of breast cancer in Poland, 7 and found that only one of 17 affected sisters was a phenocopy, and that one of 72 non-carrier relatives had developed breast cancer. The subject's mother was also diagnosed with bilateral breast cancer (at the ages of 48 and 59); however, she was found to be mutation-negative. [...]owing to the presence of a case of bilateral breast cancer in the family, which was not accounted for by the familial mutation, this subject was considered to be at greater risk, despite the negative result.